Practical Active Learning Stations to Transform Existing Learning Environments Into Flexible, Active Learning Classrooms - Eickholt, Jesse; Johnson, Matthew R.; Seeling, Patrick (IEEE transactions on education, 2021)
Contribution: Practical active learning stations (PALSs)-equipped classrooms function similar to prototypical active learning classrooms (ALCs). They support student collaboration and active learning pedagogies but at a fraction of the cost. Background: Active learning pedagogies and active learning technology are revitalizing STEM education and their use has led to an increase in student performance and satisfaction with the learning environment in postsecondary settings. An obstacle to increasing access to ALCs is the cost of constructing such learning environments. To address this challenge, a means to retrofit an existing computer laboratory into an ALC by making use of economy hardware and open-source software was devised. Intended Outcomes: In the context of an introductory sequence of programming courses (i.e., CS1 and CS2), students in a PALS-equipped classroom would perform as well as students in a prototypical ALC. Application Design: A quasi-experimental study was employed to compare the overall student performance across learning environments. Student performance was measured by the final exam score and overall course score. Throughout the study, the PALS-equipped classroom was paired five different times in head-to-head comparisons with either a prototypical ALC or a traditional classroom. Findings: The focus of the study was the potential effects of classroom type on students' final exam score and the overall course score. A statistically significant effect was found for only one measure, which was that students in the PALS classroom in CS1 scored higher on their overall course score even when accounting for demographic differences and the pretest measure. There were no other significant effects for classroom type, either on the final exam score for either course or the overall course score in CS2.